VOICES OF EXPERIENCES _CRAFTING YOUR PROFESSORIAL IDENTITY LESSONS FROM A LECTURER S JOURNEY - Mazlina, Abdul Majid (Faculty of Computing, 2024)
Crafting your professorial identity in academia involves cultivating roles, values, beliefs, and behaviors that define your professional persona. This identity is crucial for demonstrating quality excellence in teaching, research, leadership, mentoring, and community engagement, which can lead to various forms of recognition.